An Analysis of Hydro-energy Deficit in Nepal (Pravaha, 2020)
Even though Nepal has a huge hydropower capacity, it has not been able to fully exploit this vast resource for economic growth. Despite having access to electricity, the country's power sector is underperforming, with supply shortages, reliability issues, and restricted access. Nepal has been able to produce about three percent of the economic viability and less than two percent of the total potentiality. If the investment priority is made in energy sector, it contributes sufficiently to the national economy. Still there is energy deficit in Nepal basically in dry season due to lower production and high demand.